2006
DOI: 10.1373/clinchem.2005.065417
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α −308G>A Allelic Variant Modulates Iron Accumulation in Patients with Hereditary Hemochromatosis

Abstract: Background:In vitro and animal studies suggest that tumor necrosis factor ␣ (TNF-␣) modulates intestinal iron transport. We hypothesized that the effect of TNF-␣ might be particularly relevant if iron absorption is not effectively controlled by the HFE gene. Methods: In patients with homozygous C282Y hemochromatosis, we investigated the influence of TNF-␣ ؊308G>A allelic variant on total body iron overload, determined in all patients by measuring iron removed during depletion therapy, and hepatic iron index an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 51 publications
3
19
0
Order By: Relevance
“…5,6 Association studies between genetic markers and disease phenotype have given conflicting results. [7][8][9][10][11][12][13][14] More recently, candidate gene studies revealed significant associations between single nucleotide polymorphisms (SNPs) in genes involved in iron metabolism and indices of iron overload in p.C282Y homozygotes. Milet et al focused on two biologically relevant gene categories: genes involved in non-HFE-hereditary hemochromatosis (TFR2, HAMP, and SLC40A1) and genes involved in the regulation of hepcidin expression (BMP2, BMP4, HJV, SMAD1, 4 and 5, and IL6).…”
Section: Hfe-hereditarymentioning
confidence: 99%
“…5,6 Association studies between genetic markers and disease phenotype have given conflicting results. [7][8][9][10][11][12][13][14] More recently, candidate gene studies revealed significant associations between single nucleotide polymorphisms (SNPs) in genes involved in iron metabolism and indices of iron overload in p.C282Y homozygotes. Milet et al focused on two biologically relevant gene categories: genes involved in non-HFE-hereditary hemochromatosis (TFR2, HAMP, and SLC40A1) and genes involved in the regulation of hepcidin expression (BMP2, BMP4, HJV, SMAD1, 4 and 5, and IL6).…”
Section: Hfe-hereditarymentioning
confidence: 99%
“…Considerable effort has been expended, particularly by our laboratory [52][53][54][55][56][57][58] but also by others [59][60][61][62][63][64][65][66][67] to find mutations that interact with HFE mutations to increase or decrease the penetrance. These efforts have been virtually entirely fruitless.…”
Section: Genetic Modifiers Of Hereditary Hemochromatosismentioning
confidence: 99%
“…Studies in patients with hereditary hemochromatosis have found differing results with the TNF Ϫ308 A allele. One study found a trend toward lower ferritin levels and protection from liver damage, 24 another increased iron loading 25 and 2 studies found no effect. 42,43 These studies were in iron-overloaded adults rather than in children at risk of iron deficiency and the numbers of TNF Ϫ308 AA homozygotes were few (n ϭ 0-2).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the TNF Ϫ308 and the TNF Ϫ238 promoter polymorphisms were found to alter the phenotypic expression of hereditary hemochromatosis. 24,25 The TNF Ϫ308 polymorphism was associated with an increased risk of severe anemia in low-birth-weight children in Kenya, 26 although not severe malaria anemia. 26,27 The TNF Ϫ238 polymorphism was associated with an increased risk of severe malarial anemia in Gambian children.…”
Section: Introductionmentioning
confidence: 99%